TIMELINESS OF FINANCIAL REPORTING IN INDONESIA STOCK EXCHANGE - Irmalis, Amsal; Kariza, Nur; Muzakir, Muzakir (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2021)
The aims of this research is to find out the empirical evidence of the factors affecting the financial reporting timeliness of food and beverage companies listed on Indonesia stock exchange. The factors tested in this research are profitability. The population of the research are 26 food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2019. Purposive sampling method were used to draw out the samples out of population. The hypotheses were tested using logistic regression at a 5 percent significance level. The results of the research indicated that the profitability, leverage and liquidity had no effect on the timeliness of financial reporting of the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange.